Implementasi Program Kampus Mengajar sebagai Upaya Peningkatan Literasi dan Numerasi Siswa SMP Negeri 1 Matesih Kabupaten Karanganyar - Irawati, Novi; Prasetyo, Hendi; Ahmad Sobari, Haris (PELITA NUSA TENGGARA, 2025)
Community service activities are a real manifestation of the role of academics in supporting the improvement of the quality of education. The Kampus Mengajar program is designed as one of the solutions to improve students' literacy and numeracy skills, especially at SMP Negeri 1 Matesih, Karanganyar Regency. This article reviews the program's implementation as a form of contribution to the world of education, by involving students, teachers, students, and the education community to improve literacy and numeracy skills. The methods applied refer to a participatory approach, including student mentoring, teacher training, and parental involvement in supporting the learning process. The evaluation results show that student involvement in this program contributes to increasing students' interest in reading and their understanding of numeracy. This program is expected to be a model for other schools in developing the quality of education sustainability.